2017
DOI: 10.1371/journal.pone.0180884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kluyveromyces marxianus supplementation on immune responses, intestinal structure and microbiota in broiler chickens

Abstract: To investigate the effects of Kluyveromyces marxianus on immune responses, intestinal structure and microbiota in broilers, 840 1-d-old broiler chicks were randomly divided into seven groups (eight replicates) and were fed basal diets without or with 0.25, 0.50, 1.0, 1.5, 2.0, and 2.5 g/kg of K. marxianus (2.0×1010 CFU/g). Serum and intestine samples were collected at 21 d of age. The results showed that increasing K. marxianus addition linearly reduced feed conversion ratio but linearly elevated relative thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
2
22
0
2
Order By: Relevance
“…In accordance with our findings, Gheisari and Kholeghipour (2006) observed a significant increase in relative bursa weight in broilers fed ration containing powdery yeast compared to other treatments. Moreover, Wang et al (2017) reported that KM has a positive effect in broiler immune organs. However, some studies have reported that supplementation of YC did not influence carcass characteristics of broilers (Özsoy and Yalçin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with our findings, Gheisari and Kholeghipour (2006) observed a significant increase in relative bursa weight in broilers fed ration containing powdery yeast compared to other treatments. Moreover, Wang et al (2017) reported that KM has a positive effect in broiler immune organs. However, some studies have reported that supplementation of YC did not influence carcass characteristics of broilers (Özsoy and Yalçin.…”
Section: Discussionmentioning
confidence: 99%
“…YC reportedly has the capability to increase villus height and intestinal surface area, thus improving nutrients absorption and, as a consequence, digestibility in broilers (Adebiyi et al, 2012). Accordingly, Wang et al (2017) reported that KM supplementation improves the intestinal structure in broilers. A combination of these factors likely caused higher DM digestibility in MYC-fed broilers in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these investigations, in our study, we selected primers targeting the V3-V4 regions of the 16S rRNA gene. www.nature.com/scientificreports www.nature.com/scientificreports/ The complete intestinal structure is essential for digestive and absorptive functions which are intimately associated with the morphological transformations in villus length and crypt depth 36,37 . In the current study, NIBV infection increased the crypt depth and lowered the ratio of villus height to crypt depth in the ileum compared to those in the INC group.…”
Section: Discussionmentioning
confidence: 99%